The Role of Mammography in Early Detection of Breast Cancer: A Case Collection Report - Lilik Lestari; Muhammad Harris Sis Sulthansyah (RSUP Dr. Kariadi, 2025)
Background: Breast cancer is still the main cause of death in women, both globally and nationally. Therefore, mammography screening needs to be carried at to detect breast cancer early. Cases Presentation: This paper presents the mammography findings of the 83 patients at dr. Ario Wirawan Pulmonary Hospital, Salatiga, Indonesia. Mammography examination used projection cuts, namely craniocaudal (CC) and mediolateral oblique (MLO). The classification used for this case series is BI-RADS. Discussion: The results showed that of the 83 patients examined with mammography, 2 patients showed BI-RADS 4, indicating breast cancer, and 9 patients showed BI-RADS 2, indicating benign tumors. This case series report is consistent with previous studies explaining that mammography is important for making an accurate diagnosis of breast cancer between benign and malignant calcifications. Conclusion: Mammography has a role in the early detection of breast cancer. Mammography examination using CC and MLO projections is a standard procedure that aims to obtain high-quality breast images and provide accurate information for early diagnosis of breast cancer.